2023
DOI: 10.3389/fnins.2022.1100642
|View full text |Cite
|
Sign up to set email alerts
|

A dual-task gait test detects mild cognitive impairment with a specificity of 91.2%

Abstract: BackgroundMild cognitive impairment (MCI) is a valuable intervention window in the progress of senile dementia, but the question of how to easily and conveniently detect MCI in the community remains unanswered. Gait performance reflects cognitive function, but how to reliably detect MCI through gait testing is still being explored.ObjectiveTo develop a dual-task gait testing method that could reliably detect MCI in the community.MethodsA cross-sectional diagnostic study was conducted in 111 older adults (mean … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 37 publications
0
1
1
Order By: Relevance
“…Specifically, our study found that DT-GS, DT-SL, and DT-TV parameters showed approximately a 10% improvement in predicting MCI and dementia compared to single-task (in terms of AUC). This improvement is higher than what has been reported in other studies, where typically only about a 6% improvement is observed ( Wang X. et al, 2023 ; Wang Y. et al, 2023 ). Moreover, our study demonstrated that dual-task gait parameters collected using smart gait devices achieved a dementia prediction rate of up to 90%, highlighting the potential of wearable devices in screening for dementia.…”
Section: Discussioncontrasting
confidence: 76%
“…Specifically, our study found that DT-GS, DT-SL, and DT-TV parameters showed approximately a 10% improvement in predicting MCI and dementia compared to single-task (in terms of AUC). This improvement is higher than what has been reported in other studies, where typically only about a 6% improvement is observed ( Wang X. et al, 2023 ; Wang Y. et al, 2023 ). Moreover, our study demonstrated that dual-task gait parameters collected using smart gait devices achieved a dementia prediction rate of up to 90%, highlighting the potential of wearable devices in screening for dementia.…”
Section: Discussioncontrasting
confidence: 76%
“…The cognitive task may be the recital of the months in reverse order [12] or naming animals shown randomly on a screen, which solves the memorization issue in the cognitive task [13]. The assessment takes only minutes to perform and yields a wealth of data.…”
Section: Introductionmentioning
confidence: 99%